Practical Aspects of Use of Perspective Ornamental plants of the Genus Anemone L. for the Landscaping in Forest-Steppe of Ukraine - Pereboichuk, Oksana (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Тhe results of the introduction of decorative taxons of the genus Anemone L. in Forest-Steppe of Ukraine are represented in this article. On the basis of scientific principles, the main options for combining them in landscape compositions have been developed. Behind the life form of plants, taxa were grouped into a five groups: plants with long rhizomes and single flowers, ephemeroids (Anemone altaica Fisch. ex Ledeb., Anemone nemorosa L., Anemone ranunculoides L.); tuberous rhizomes (Anemone blanda Schott & Kotschy); with vertical caudexes and a taproot, or a mixed root system (Anemone multifida Poir., Anemone narcissiflora L., Anemone rivularis Wall., Anemone rivularis var. flore-minore Maxim.); roots sprouts Anemone (Anemone canadensis L., Anemone dichotoma L., Anemone hupehensis Hort. Ex Boynton, Anemone hupehensis var. japonica (Thunb.) Bowles & Stearn, Anemone sylvestris L., Anemone tomentosa (Maxim.) S.F. Pei); with a fibrous root system (Anemone cylindrica A.Gray, Anemone virginiana L., Anemone virginiana var. alba (Oakes) Alph.Wood.). By selected groups were analyzed their potential growth opportunities, the formation of habit and offered posibilities of use in the landscape under the conditions of the Forest-Steppe of Ukraine. Anemone are more attractive when used in the landscape style. The assortment of taxons is developed for various elements of floral-decorative design: single plantings, group plantings, single-species groupings, rock gardens, мixboxers, rabatte, landscaping around a water basins, single species gardens, natural garden, garden cognitive compositions etc. Thus, the use of plants of the Anemone species for the gardening in the conditions of the Forest-steppe of Ukraine will enable enrichment of the taxonomic assortment of flower-decorative plants and expand the opportunities for the formation of diverse, durable, highly decorative landscape compositions.